Response of a co-culture model of epithelial cells and gingival fibroblasts to zoledronic acid - Basso, Fernanda Gonçalves; Soares, Diana Gabriela; Pansani, Taisa Nogueira; Turrioni, Ana Paula Silveira; Scheffel, Débora Lopes; Hebling, Josimeri; Costa, Carlos Alberto de Souza (FapUNIFESP (SciELO), 2016)
Osteonecrosis of the jaw is an adverse effect of bisphosphonates. While the etiopathogenesis of this condition has been investigated, the interactions and effects of bisphosphonates on oral mucosa cells remain unclear. It is hypothesized that cell culture models, such as co-culture or three-dimensional cell culture models, can provide valuable insight. Therefore, the aim of this study was to evaluate the effects of zoledronic acid (ZA) on epithelial cells and gingival fibroblasts in a co-culture model. Briefly, epithelial cells were seeded on transwell inserts and gingival fibroblasts were seeded in the lower well of 24-well plates. The latter were treated with ZA (5 μM) for 24 or 48 h. Cell viability and synthesis of the inflammatory chemokine, CCL2, were subsequently assessed. Data were subjected to statistical analysis with a 5% significance level. In the presence of ZA, the epithelial cells exhibited significant toxicity in both cell culture models and at both time points. However, greater cytotoxicity was observed in the co-culture model. Greater viability for the gingival fibroblasts was also associated with the co-culture model, and ZA-mediated toxicity was observed for the 48 h time point. ZA promoted a significant increase in CCL2 synthesis in both sets of cells, with greater CCL2 synthesis detected in the gingival fibroblasts. However, this effect was diminished in the co-culture model. Taken together, these results confirm the specific response patterns of the cells seeded in the co-culture model and also demonstrate the protective mechanism that is mediated by epithelial/mesenchymal cell interactions upon exposure to ZA.